A study of diet in older community-dwelling adults in the UK during the COVID-19 pandemic: Findings from the Southampton Longitudinal Study of Ageing (SaLSA) - Laskou, Faidra; Bevilacqua, Gregorio; Westbury, Leo D.; Bloom, Ilse; Aggarwal, Pritti; Cooper, Cyrus; Patel, Harnish P.; Dennison, Elaine (Frontiers in Nutrition, 2023)
Introduction Adequate nutrition is important for health in later life. Older adults are especially vulnerable to adverse outcomes following infection by COVID-19 and have commonly spent a disproportionate time within their own homes to reduce risk of infection. There are concerns that advice to shield may have led to malnutrition as older adults may modify daily routines including usual shopping habits. The aims of this study were to report self-reported pandemic-related changes in diet and examine lifestyle and medical correlates of these changes in older UK community-dwelling adults. Methods We recruited 491 participants from the city of Southampton, UK. Participants completed a postal questionnaire in summer/autumn 2021, over a year after the first UK national lockdown was announced. The questionnaire ascertained demographic and lifestyle factors, in addition to number of comorbidities, nutrition risk scores, and presence of frailty. Associations between these participant characteristics in relation to self-reported changes in diet quality (lower, similar or higher when compared to before the first lockdown) were examined using ordinal logistic regression. Results Median (lower quartile, upper quartile) age was 79.8 (77.0, 83.7) years. Overall, 11 (4.9%) men and 25 (9.4%) women had poorer diet quality compared to before the first UK lockdown. The following participant characteristics were associated with increased risk of being in a worse category for change in diet quality after adjustment for sex: lower educational attainment (p = 0.009); higher BMI (p < 0.001); higher DETERMINE (a malnutrition assessment) score (p = 0.004); higher SARC-F score (p = 0.013); and self-reported exhaustion in the previous week on at least 3 days (p = 0.002). Conclusions Individuals at higher nutritional risk were identified as reporting increased risk of deterioration in diet quality during the pandemic. Further investigation of the factors leading to these changes, and an understanding of whether they are reversible will be important, especially for future pandemic management.